The New Threat from Islamic Militancy - Burke, Jason (London The Bodley Head, 2015)
From Syria to Somalia, from Libya to Indonesia, from Yemen to the capitals of Europe, Islamic militancy appears stronger, more widespread and more threatening than ever. ISIS and other groups, such as Boko Haram, together command significant military power, rule millions and control extensive territories. This is a guide to Islamic militancy.
Include Notes and Index
Keywords: Terrorism--Religious aspects--Islam -- Terrorism -- Islamic countries -- Islamic fundamentalism -- IS (Organization)